ASSESSING THE IMPACT OF TELECOMMUNICATION AND OIL SECTORS ON NIGERIA’S GROSS DOMESTIC PRODUCT USING VECTOR ERROR CORRECTION MODEL - S. M. , MAHMUD; G. K., MUSA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The contributions of oil sector and telecommunication sectors to Gross Domestic Product (GDP) in Nigeria cannot be overemphasized. Thus, this study assesses the impact of telecommunication and oil sectors on gross domestic product using the Vector Error Correction Model (VECM). To achieve this, the annual data from 1981 to 2021 was collected from the 2021 Central Bank of Nigeria Statistical bulletin. The Augmented Dickey Fuller test revealed that all the variables are stationary after first difference and they are also co-integrated. The VECM was estimated and the long run coefficient shows that the oil sector has significant positive impact on gross domestic product while telecommunication sector has negative and significant impact on GDP in the long run. Evidence from variance decomposition revealed that the oil sector and telecommunication sector explain the variance in GDP by about 33.4% and 66.3% respectively. Based on these findings, it was recommended that government should reexamine the telecommunication sector by way of increasing tax base and introducing new taxes in such a way that it does not distort the working of the economy but to increase the economic growth.